2022
DOI: 10.1186/s12981-022-00453-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and reasons for switching anti-retroviral regimen among HIV-infected youth in a large township of South Africa (2002–2019)

Abstract: Background There are limited data exploring antiretroviral therapy (ART) changes and time to change among South Africa young people living with HIV/AIDS. Objective We describe the time to first drug switch, which includes ART regimen change (three drug switch) and substitutions (single drug switch). We describe common reasons for ART switch among young people aged 10 to 24 years in South Africa. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Indeed, the use of new therapeutic agents in combination with tenofovir (the most commonly used antiviral against HBV in PLWH) have less deleterious effect on steatosis and they are thought to potentially decrease risk of HCC by decreasing the risk of cirrhosis. Nonetheless, the specific effect of ART on HCC has not been well studied and many countries in Africa still use relatively older treatments which can increase the risk of liver dysfunction [ 23 , 34 ] .…”
Section: Hiv-hbv Coinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the use of new therapeutic agents in combination with tenofovir (the most commonly used antiviral against HBV in PLWH) have less deleterious effect on steatosis and they are thought to potentially decrease risk of HCC by decreasing the risk of cirrhosis. Nonetheless, the specific effect of ART on HCC has not been well studied and many countries in Africa still use relatively older treatments which can increase the risk of liver dysfunction [ 23 , 34 ] .…”
Section: Hiv-hbv Coinfectionmentioning
confidence: 99%
“…An expected consequence of this, is the dramatically increased risk of developing complications from other associated chronic diseases, such as cirrhosis and HCC [32] . Patients on ART, on the other hand, have a higher risk of hepatotoxicity after starting the therapy [33] . Novel ART has decreased the toxic effect of these medications in the liver.…”
Section: The Effect Of Hiv-hbv Coinfection On the Livermentioning
confidence: 99%
“…Studies have demonstrated that a strategic switch from one ART regimen to another can lead to a significant reduction in viral load, thereby enhancing treatment efficacy. By targeting distinct mechanisms of action and overcoming resistance pathways, ART switches offer a renewed opportunity to achieve and maintain the durable suppression of the virus [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%